Liquid membrane technology: fundamentals and review of its applications - San Román, M.F; Bringas, E; Ibañez, R; Ortiz, I (Journal of chemical technology and biotechnology (1986), 2010)
OVERVIEW: During the past two decades, liquid membrane technology has grown into an accepted unit operation for a wide variety of separations. The increase in the use of this technology owing to strict environmental regulations and legislation together with the wider acceptance of this technology in preference to conventional separation processes has led to a spectacular advance in membrane development, module configurations, applications, etc.IMPACT: Liquid membrane technology makes it possible to attain high selectivity as well as efficient use of energy and material relative to many other separation systems. However, in spite of the known advantages of liquid membranes, there are very few examples of industrial applications because of the problems associated with the stability of the liquid membrane.APPLICATIONS: Liquid membrane technology has found applications in the fields of chemical and pharmaceutical technology, biotechnology, food processing and environmental engineering. On the other hand, its use in other fields, such as in the case of hydrogen separation, the recovery of aroma compounds from fruits, the application of ionic liquids in the membrane formulation, etc., is increasing rapidly. Copyright